Free Education Review of Social Exchange Theory (Phenomenological Study of Overseas Scholarship Recipients) - Bambang Yuniarto; Bambang Bahrul Ulum; Wilda’nun Muholadun; Dzuan Tira Fazari (Journal of Social Research, 2023)
The researcher found that there were still several students who misunderstood the purpose of using the opportunities provided by the government not for academic purposes but for other things outside of academia, this is where the use of scholarships among students is still not optimal in utilizing the scholarships. This study uses a qualitative phenomenological approach with the interview method. The research subjects were 3 (three) people. Data collection techniques with observation and interviews. The data validation technique uses source triangulation by collecting similar data and information from a variety of different sources. Based on the analysis of the results of the interviews and their relation to social exchange theory, it can be seen that scholarship recipients have the advantage of receiving free education at leading schools and universities in the Islamic world. They have the advantage of getting a lot of authentic Islamic learning resources from texts, manuscripts, and relics of past Islamic glories at no cost or for free. However, to get the scholarship, they must make sacrifices, namely by following a strict selection process, and after being accepted as a student or students they must achieve according to the requirements of the institution. And 1 in 3 subjects or informants is even required to do community service in channeling institutions after their education is complete. Because this is a reciprocity to the distributor of the scholarship and is a sacrifice that must be made by the scholarship recipient